2011
DOI: 10.1007/s00595-010-4468-9
|View full text |Cite
|
Sign up to set email alerts
|

Pleural defect repair with an overlapping method using fibrin glue-coated collagen fleece

Abstract: Pleural defects repaired using an overlapping method with an MOW of 6 mm were able to withstand airway pressures ≥ 40 cmH(2)O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In addition, the pleural area around the defects adhered to the TachoSil, and these histologic changes were responsible for prevention of air leakage. A previous study 14 demonstrated the histologic changes associated with the use of fibrin glue-coated collagen fleece to repair pleural defects until POD 7, and these findings were consistent with our results. However, the changes in the TachoSil and their long-term effects on the lung parenchyma have remained unclear.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the pleural area around the defects adhered to the TachoSil, and these histologic changes were responsible for prevention of air leakage. A previous study 14 demonstrated the histologic changes associated with the use of fibrin glue-coated collagen fleece to repair pleural defects until POD 7, and these findings were consistent with our results. However, the changes in the TachoSil and their long-term effects on the lung parenchyma have remained unclear.…”
Section: Discussionsupporting
confidence: 93%
“…We think fi brosis could function as a mechanical barrier between the bronchial stump and pleural cavity. 13,14) Thus, the prevention of communication between the bronchial stump and the pleural cavity could be mediated by fi brosis and adhesion. Lastly, while many studies support the benefi t of stump coverage, controversy remains concerning which coverage technique should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen fleece maintains the strength of tissue by adhering to the tissue and forming a three-dimensional structure. Matsutani and Ozeki10 examined the efficacy of overlapping of collagen fleece to repair pleural defects. They concluded that pleural circular defects 6 mm in diameter with overlapping of collagen fleece could withstand airway pressure of 40 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%